2011
DOI: 10.1002/jsfa.4489
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry extract inhibits oleic acid‐induced lipid accumulation via reduction of lipogenesis and promotion of hepatic lipid clearance

Abstract: Our study suggests that the hypolipidemic effects of MWE occur via phosphorylation of AMPK and inhibition of lipid biosynthesis. Therefore, the mulberry extract may be active in the prevention of fatty liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 52 publications
2
46
1
Order By: Relevance
“…Similarly, mulberry leaves have also shown promising biological effects (Jeszka-Skowron et al, 2014;Wu et al, 2013). Previous studies have shown the anti-hyperlipidemic, anticancer, liver-protecting, anti-inflammatory, and anti-obesity effects of mulberry water extracts (Hsu et al, 2012;Jeong, Jang, Kim, Kwon, & Kim, 2010;Ou et al, 2011Ou et al, , 2013Park, Lee, & Kim, 2013;Peng et al, 2011) as well as their ability to inhibit the development of atherosclerosis in cholesterol-fed rabbits (Chen et al, 2005). Because atherosclerosis and restenosis are complex and multifactorial processes, our aim was to identify the active polyphenols in mulberry polyphenol extracts (MPEs) and investigate the mechanisms underlying their inhibition of VSMCs proliferation and thereby atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mulberry leaves have also shown promising biological effects (Jeszka-Skowron et al, 2014;Wu et al, 2013). Previous studies have shown the anti-hyperlipidemic, anticancer, liver-protecting, anti-inflammatory, and anti-obesity effects of mulberry water extracts (Hsu et al, 2012;Jeong, Jang, Kim, Kwon, & Kim, 2010;Ou et al, 2011Ou et al, , 2013Park, Lee, & Kim, 2013;Peng et al, 2011) as well as their ability to inhibit the development of atherosclerosis in cholesterol-fed rabbits (Chen et al, 2005). Because atherosclerosis and restenosis are complex and multifactorial processes, our aim was to identify the active polyphenols in mulberry polyphenol extracts (MPEs) and investigate the mechanisms underlying their inhibition of VSMCs proliferation and thereby atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several natural products from plant origin have been suggested to be capable of preventing obesity via regulating hyperlipidemia and reducing adipose tissue mass, thus suppressing the occurrence of the metabolic, hepatic, and cardiovascular alterations associated with obesity [11][12][13]. Many studies have indicated that antioxidant phenolic compounds have been used in cellular and animal models for the treatment of obesity and hypolipidemic effects [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Group (4) is the HFD-treated rats for 1 12 consecutive . Groups (5) and (6) are obese rats treated for 6 weeks with 300 mg/kg body weight of ethanolic extract of white and purple berry (HFD/MA and HFD/MR, respectively). Group (7) is the obese rats treated for 6 weeks with antiobesity standard drug OR (12 mg/kg body weight) (HFD/OR).…”
Section: Experimental Designmentioning
confidence: 99%
“…The mulberry fruits (Morus alba L. [MA] and Morus rubra [MR]) distributed widely in Asia as a food containing potential health benefits beyond the traditional nutrients they provide [6]. It is rich in polyphenolic compounds including rutin, quercetin, and 1-deoxynojirimycin (DNJ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation